Optic Neuritis in an Adult Patient with Chickenpox - Ana Rita Azevedo; Rita Simões; Filipe Silva; Susana Pina; Cristina Santos; Peter Pêgo; Filomena Silva; Susana Teixeira (Case Reports in Ophthalmological Medicine)
Central nervous system involvement in a patient with primary infection with Varicella zoster virus is rare, especially in the immunocompetent adult. In particular, isolated optic neuritis has been described in a small number of cases. The authors present a case of optic neuritis in an immunocompetent patient. A 28-year-old woman presented to the emergency room with a history of headaches during the previous week, without visual symptoms. The examination was unremarkable, except for a rash suggestive of chickenpox and hyperemic and edematous optic disc, bilaterally. Visual acuity and neurological examination were normal. Two days later, she complained of pain on eye movement and decreased visual acuity, which was 20/32 in her right eye and 20/60 in her left eye. Four days after admission, her visual acuity started to improve, and two months later, she had 20/20 visual acuity in both eyes. To our knowledge, this is the first reported case of an immunocompetent adult in which a Varicella zoster virus associated optic neuritis presented with fundoscopic changes before decreased visual acuity. This suggests that this condition may be underdiagnosed in asymptomatic patients.